A lithium iron phosphate positive electrode material and its preparation method and application

By using carbon quantum dots containing amino groups and amorphous carbon cladding on the lithium iron phosphate positive electrode material, the problem of insufficient conductivity and stability of the material is solved, and efficient electrochemical performance and long cycle life are achieved.

CN115360342BActive Publication Date: 2025-04-29EVE POWER CO LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202211204299.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-09-29
Publication Date
2025-04-29
Estimated Expiration
2042-09-29

AI Technical Summary

Technical Problem

Lithium iron phosphate positive electrode material has problems such as low ion diffusion rate and poor conductivity, which affects its rate performance and low temperature performance. At the same time, it is insufficient stability in complex use environments, making it difficult to improve output power and stability at the same time.

Method used

A cladding layer containing carbon quantum dots and amorphous carbon was used to coat the lithium iron phosphate matrix by spray drying, and two-step heat treatment was performed to form a uniform cladding layer to improve conductivity and stability.

Benefits of technology

The conductivity improvement and structural stability of lithium iron phosphate positive electrode material have been achieved, and the cycle life has been extended. The initial specific capacity at 0.1C can reach more than 164.92mAh/g, and the capacity retention rate after 40 cycles can reach more than 83.5%.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115360342B_ABST
    Figure CN115360342B_ABST
Patent Text Reader

Abstract

The present invention provides a lithium iron phosphate positive electrode material and a preparation method and application thereof. The lithium iron phosphate positive electrode material comprises a lithium iron phosphate matrix and a coating layer coated on the surface of the lithium iron phosphate matrix; the coating layer comprises carbon quantum dots containing amino groups and amorphous carbon. The lithium iron phosphate positive electrode material provided by the present invention comprises carbon quantum dots containing amino groups in the coating layer, so that the coating is more uniform and the conductivity of the lithium iron phosphate is improved. At the same time, the amino groups in the carbon quantum dots can stabilize the HF and water generated by the lithium ion battery during use, prevent HF and water from damaging the positive electrode material, and extend the cycle life.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of lithium ion batteries and relates to a lithium iron phosphate positive electrode material and a preparation method and application thereof. Background Art

[0002] Lithium iron phosphate, as a positive electrode material for lithium-ion batteries, has a theoretical capacity of up to 170mAh / g. It was first reported by Goodenough et al. in 1997. It has become the first choice for positive electrode materials for power and energy storage lithium-ion batteries due to its wide source of raw materials, low price, good thermal stability, high voltage platform, long cycle life, non-toxicity, and no oxygen evolution under abuse conditions. It can solve safety problems that lithium cobalt oxide and other existing positive electrode materials cannot solve.

[0003] However, due to the low ion diffusion rate and poor conductivity of LiFePO4, the rate performance and low temperature performance of LiFePO4 are greatly affected. At the same time, due to the complex use environment of lithium-ion batteries, higher requirements are also placed on the stability of positive electrode materials. To solve such problems, lithium iron phosphate is usually required to be modified, but most of them can only solve a single problem. Improving the output power of lithium iron phosphate while ensuring its stability is the main challenge facing lithium iron phosphate positive electrode materials.

[0004] CN103384006A discloses a method for preparing a lithium iron phosphate / carbon composite material, comprising the following steps: uniformly mixing a trivalent iron salt, iron powder, a lithium source and a phosphorus source; adding a carbon source, a ball milling agent and a reaction aid to the above mixture, and fully ball milling; calcining the precursor obtained after ball milling at 600-800°C in an inert gas environment to obtain a lithium iron phosphate / carbon composite material. Although the cycle performance of the prepared positive electrode material is improved, its rate performance is general, which limits the application of the material in high-rate batteries.

[0005] CN107240696A discloses a method for preparing carbon-coated lithium iron phosphate, carbon-coated lithium iron phosphate and lithium ion battery, and relates to the technical field of lithium ion batteries. The preparation method is to first mix part of the carbon source with iron phosphate, grind and dry, and then pre-sinter, then mix the pre-sintered material, lithium source and part of the carbon source, grind and dry, and then sinter again to obtain carbon-coated lithium iron phosphate, and through two carbon source coatings and two sintering processes, the surface of the prepared carbon-coated lithium iron phosphate is double-coated with a carbon layer, but the document is still a single modification, and it is difficult to ensure its stability and high output power at the same time.

[0006] Therefore, how to simultaneously improve the stability and electrochemical performance of lithium iron phosphate positive electrode materials is a technical problem that needs to be solved urgently. Summary of the invention

[0007] The purpose of the present invention is to provide a lithium iron phosphate positive electrode material and a preparation method and application thereof. The lithium iron phosphate positive electrode material provided by the present invention includes carbon quantum dots containing amino groups in the coating layer, so that the coating is more uniform and the conductivity of the lithium iron phosphate is improved. At the same time, the amino groups in the carbon quantum dots can stabilize the HF and water generated during the use of the lithium ion battery, prevent HF and water from damaging the positive electrode material, and extend the cycle life.

[0008] In order to achieve the purpose of the invention, the present invention adopts the following technical solutions:

[0009] In a first aspect, the present invention provides a lithium iron phosphate positive electrode material, which includes a lithium iron phosphate matrix and a coating layer coated on the surface of the lithium iron phosphate matrix; the coating layer includes carbon quantum dots containing amino groups and amorphous carbon.

[0010] The lithium iron phosphate positive electrode material provided by the present invention comprises carbon quantum dots containing amino groups in the coating layer, so that the coating is more uniform and the conductivity of the lithium iron phosphate is improved. At the same time, the amino groups in the carbon quantum dots can stabilize HF and water generated during the use of the lithium ion battery, prevent HF and water from damaging the positive electrode material, and extend the cycle life.

[0011] In the present invention, if the carbon quantum dots do not contain amino groups, it is impossible to stabilize the HF and water generated during the use of the lithium-ion battery. If the carbon quantum dots containing amino groups are simply coated without adding amorphous carbon, the positive electrode structure will be unstable. If only carbon coating is performed, it is impossible to stabilize the HF and water generated during the use of the lithium-ion battery.

[0012] Preferably, the D50 of the carbon quantum dots containing amino groups is 2 to 5 nm, such as 2 nm, 3 nm, 4 nm or 5 nm.

[0013] In the present invention, if the D50 of the carbon quantum dots containing amino groups is too large, the gram capacity will be reduced.

[0014] Preferably, the D50 of the lithium iron phosphate is 600-700 nm, for example, 600 nm, 610 nm, 620 nm, 630 nm, 640 nm, 650 nm, 660 nm, 670 nm, 680 nm, 690 nm or 700 nm.

[0015] Preferably, the mass of the coating layer is 0.1-0.2% of the mass of the lithium iron phosphate positive electrode material, for example, 0.1%, 0.11%, 0.12%, 0.13%, 0.14%, 0.15%, 0.16%, 0.17%, 0.18%, 0.19% or 0.2%, etc.

[0016] Preferably, the mass of the carbon quantum dots containing amino groups is 20-25% of the mass of the coating layer, for example 20%, 20.5%, 21%, 21.5%, 22%, 22.5%, 23%, 23.5%, 24%, 24.5% or 25%, etc.

[0017] In the present invention, if the mass ratio of carbon quantum dots containing amino groups to amorphous carbon is too large, that is, the carbon quantum dots process is not conducive to the stability of the positive electrode structure, while if the mass ratio is too small, it will affect the absorption of HF and water.

[0018] In a second aspect, the present invention provides a method for preparing the lithium iron phosphate positive electrode material as described in the first aspect, the preparation method comprising the following steps:

[0019] The carbon quantum dots containing amino groups and the carbon source are coated on the surface of the lithium iron phosphate matrix by a spray drying method, and then heat treated to obtain the lithium iron phosphate positive electrode material.

[0020] In the present invention, the carbon quantum dots and the carbon source can be coated during the preparation and granulation process of the lithium iron phosphate positive electrode material, or can be directly coated with the lithium iron phosphate material through spray drying.

[0021] In the present invention, carbon quantum dots containing amino groups and carbon sources are coated by spray drying and then heat treated to obtain a uniformly coated coating layer. The preparation method is simple and does not require complicated preparation steps.

[0022] Preferably, the method for preparing the carbon quantum dots containing amino groups comprises:

[0023] The organic matter containing amino groups is mixed with citric acid, subjected to hydrothermal reaction, and freeze-dried to obtain carbon quantum dots containing amino groups.

[0024] In the present invention, carbon quantum dot powder is obtained by hydrothermal and freeze drying.

[0025] Preferably, the organic compound containing an amino group comprises ethylenediamine and / or formamide.

[0026] Preferably, the temperature of the hydrothermal reaction is 100-220°C, for example, 100°C, 110°C, 120°C, 130°C, 140°C, 150°C, 160°C, 170°C, 180°C, 190°C, 200°C, 210°C or 220°C, etc.

[0027] Preferably, the hydrothermal reaction time is 12 to 24 hours, for example, 12 hours, 15 hours, 18 hours, 20 hours, 22 hours or 24 hours.

[0028] Preferably, the freeze-drying time is 24 to 48 h, for example 12 h, 15 h, 18 h, 20 h, 24 h, 25 h, 28 h, 30 h, 33 h, 35 h, 38 h, 40 h, 43 h, 45 h or 48 h.

[0029] Preferably, the coating method comprises:

[0030] The iron source, phosphorus source and polyvinyl pyrrolidone are mixed, and the pH value is adjusted to obtain an iron phosphate solution. The iron phosphate solution, lithium source, carbon quantum dots containing amino groups and carbon source are mixed, and spray-dried for coating.

[0031] In the present invention, the formation of the ferric phosphate solution further comprises adding water.

[0032] In the present invention, during the preparation of lithium iron phosphate, the coating of carbon quantum dots containing amino groups and carbon sources is simultaneously achieved. During further heat treatment, a lithium iron phosphate material with a stable structure is formed, and uniformly coated amorphous carbon material and carbon quantum dots containing amino groups are also obtained.

[0033] Preferably, the pH value is 3 to 3.4, such as 3, 3.1, 3.2, 3.3 or 3.4.

[0034] Preferably, the spray drying temperature is 170-180°C, for example, 170°C, 171°C, 172°C, 173°C, 174°C, 175°C, 176°C, 177°C, 178°C, 179°C or 180°C, etc.

[0035] In the present invention, if the spray drying temperature is too low, it is not conducive to the carbon quantum dots and the carbon source being unable to be coated on the surface of the lithium iron phosphate matrix, while if the temperature is too high, a small amount of carbon quantum dots and the carbon source will be coated on the surface of the lithium iron phosphate matrix, resulting in carbonization.

[0036] Preferably, the heat treatment is performed under a reducing atmosphere.

[0037] In the present invention, the heat treatment is carried out in a reducing atmosphere to achieve uniform coating of the carbon quantum dots and the carbon source on the surface of the lithium iron phosphate matrix.

[0038] Preferably, the heat treatment includes performing a primary heat treatment and a secondary heat treatment in sequence.

[0039] In the present invention, after the primary heat treatment and the secondary heat treatment, it is more conducive to forming a lithium iron phosphate material with a stable structure, and at the same time, a uniformly coated amorphous carbon material and carbon quantum dots containing amino groups are obtained.

[0040] Preferably, the temperature of the primary heat treatment is 300-350°C, for example, 300°C, 305°C, 310°C, 315°C, 320°C, 325°C, 330°C, 335°C, 340°C, 345°C or 350°C.

[0041] Preferably, the time of the primary heat treatment is 5 to 8 hours, for example, 5 hours, 6 hours, 7 hours or 8 hours.

[0042] Preferably, the temperature of the secondary heat treatment is 600-800°C, for example, 600°C, 630°C, 650°C, 680°C, 700°C, 730°C, 750°C, 780°C or 800°C.

[0043] Preferably, the secondary heat treatment time is 10 to 20 h, for example, 10 h, 11 h, 12 h, 13 h, 14 h, 15 h, 16 h, 17 h, 18 h, 19 h or 20 h.

[0044] As a preferred technical solution, the preparation method comprises the following steps:

[0045] (1) mixing an organic substance containing an amino group with citric acid, subjecting it to a hydrothermal reaction at 100 to 220° C. for 12 to 24 hours, and freeze-drying it for 24 to 48 hours to obtain carbon quantum dots containing an amino group;

[0046] (2) An iron source, a phosphorus source and polyvinyl pyrrolidone are mixed, and the pH value is adjusted to 3-3.4 to obtain an iron phosphate solution, and the iron phosphate solution, a lithium source, carbon quantum dots containing amino groups and a carbon source are mixed, spray-dried for coating, and then heat-treated at 300-350° C. for 5-8 h in a reducing atmosphere, and then heat-treated at 600-800° C. for 10-20 h to obtain the lithium iron phosphate positive electrode material.

[0047] In a third aspect, the present invention further provides a lithium-ion battery, wherein the lithium-ion battery comprises the lithium iron phosphate positive electrode material as described in the first aspect.

[0048] Compared with the prior art, the present invention has the following beneficial effects:

[0049] (1) The lithium iron phosphate positive electrode material provided by the present invention includes carbon quantum dots containing amino groups and amorphous carbon in the coating layer, so that the coating is more uniform and the conductivity of lithium iron phosphate is improved. At the same time, the amino groups in the carbon quantum dots can stabilize the HF and water generated during the use of the lithium ion battery, prevent HF and water from damaging the positive electrode material, extend the cycle life, and improve the structural stability, conductive agent and cycle stability of the lithium iron phosphate positive electrode material. The battery adopts the lithium iron phosphate material provided by the present invention, regulates the quality of the carbon quantum dots in the coating layer, and adopts a two-step heat treatment method. The initial specific capacity at 0.1C can reach more than 164.92mAh / g, and the capacity retention rate after 40 cycles can reach more than 83.5%.

[0050] (2) The preparation method provided by the present invention coats the carbon quantum dots containing amino groups and the carbon source by a spray drying method to obtain a uniformly coated coating layer. The method is simple and does not require complicated preparation steps, and is suitable for actual production. BRIEF DESCRIPTION OF THE DRAWINGS

[0051] Figure 1 This is a comparison chart of the cycle performance of the batteries provided in Example 1 and Comparative Example 3. DETAILED DESCRIPTION

[0052] The technical solution of the present invention is further described below by specific implementation methods. It should be understood by those skilled in the art that the embodiments are only to help understand the present invention and should not be regarded as specific limitations of the present invention.

[0053] Example 1

[0054] This embodiment provides a lithium iron phosphate positive electrode material, the lithium iron phosphate positive electrode material comprising a lithium iron phosphate matrix (D50 is 650nm) and a coating layer coated on the surface of the lithium iron phosphate matrix; the coating layer is carbon quantum dots containing amino groups (D50 is 3nm) and amorphous carbon;

[0055] The mass of the coating layer is 0.15% of the mass of the lithium iron phosphate positive electrode material, and the mass of the carbon quantum dots containing amino groups in the coating layer accounts for 24%.

[0056] The preparation method of the lithium iron phosphate positive electrode material is as follows:

[0057] (1) preparing 0.5 mol / L ethylenediamine and citric acid solutions respectively, taking the two solutions and mixing them in a mass ratio of 1:1, placing them in a high temperature reactor, and hydrothermally reacting them at 200° C. for 12 h, passing the resulting solution through a filter membrane with a pore size of 10 nm to obtain a carbon quantum dot solution, and then freeze-drying them for 30 h to obtain a carbon quantum dot powder containing an amino group;

[0058] (2) Dissolve FeCl3 and NH4H2PO4 in deionized water, quickly mix the aqueous solutions under ultrasound and stirring, adjust the pH value to 3, add PVP to control the size of FePO4 particles, and obtain FePO4 solution; mix the prepared FePO4 solution, Li2CO3, sucrose and carbon quantum dots that meet the stoichiometric ratio in liquid phase, and obtain powder by spray drying; heat treat the obtained powder in a mixed reducing atmosphere (a mixed atmosphere of hydrogen and argon), first calcine at 350°C for 6h and then heat to 700°C for 15h to obtain the lithium iron phosphate positive electrode material.

[0059] Example 2

[0060] This embodiment provides a lithium iron phosphate positive electrode material, the lithium iron phosphate positive electrode material comprising a lithium iron phosphate matrix (D50 is 700nm) and a coating layer coated on the surface of the lithium iron phosphate matrix; the coating layer is carbon quantum dots containing amino groups (D50 is 5nm) and amorphous carbon;

[0061] The mass of the coating layer is 0.1% of the mass of the lithium iron phosphate positive electrode material, and the mass of the carbon quantum dots containing amino groups in the coating layer accounts for 20%.

[0062] The preparation method of the lithium iron phosphate positive electrode material is as follows:

[0063] (1) preparing 0.5 mol / L ethylenediamine and citric acid solutions respectively, taking the two solutions and mixing them in a mass ratio of 1:1, placing them in a high temperature reactor, and hydrothermally reacting them at 150° C. for 18 h, passing the resulting solution through a filter membrane with a pore size of 10 nm to obtain a carbon quantum dot solution, and then freeze-drying them for 24 h to obtain a carbon quantum dot powder containing an amino group;

[0064] (2) Dissolve FeCl3 and NH4H2PO4 in deionized water, quickly mix the aqueous solutions under ultrasound and stirring, adjust the pH value to 3.2, add PVP to control the size of FePO4 particles, and obtain FePO4 solution; mix the prepared FePO4 solution, Li2CO3, sucrose and carbon quantum dots that meet the stoichiometric ratio in liquid phase, and obtain powder by spray drying; heat treat the obtained powder in a mixed reducing atmosphere (a mixed atmosphere of hydrogen and argon), first calcine at 300°C for 5h and then heat to 600°C for 10h to obtain the lithium iron phosphate positive electrode material.

[0065] Example 3

[0066] This embodiment provides a lithium iron phosphate positive electrode material, the lithium iron phosphate positive electrode material comprising a lithium iron phosphate matrix (D50 is 600nm) and a coating layer coated on the surface of the lithium iron phosphate matrix; the coating layer is carbon quantum dots containing amino groups (D50 is 2nm) and amorphous carbon;

[0067] The mass of the coating layer is 0.2% of the mass of the lithium iron phosphate positive electrode material, and the mass of the carbon quantum dots containing amino groups in the coating layer accounts for 25%.

[0068] The preparation method of the lithium iron phosphate positive electrode material is as follows:

[0069] (1) preparing 0.5 mol / L ethylenediamine and citric acid solutions respectively, taking the two solutions and mixing them in a mass ratio of 1:1, placing them in a high temperature reactor, and hydrothermally reacting them at 200° C. for 24 h, passing the resulting solution through a filter membrane with a pore size of 10 nm to obtain a carbon quantum dot solution, and then freeze-drying them for 48 h to obtain a carbon quantum dot powder containing an amino group;

[0070] (2) Dissolve FeCl3 and NH4H2PO4 in deionized water, quickly mix the aqueous solutions under ultrasound and stirring, adjust the pH value to 3.4, add PVP to control the size of FePO4 particles, and obtain FePO4 solution; mix the prepared FePO4 solution, Li2CO3, sucrose and carbon quantum dots that meet the stoichiometric ratio in liquid phase, and obtain powder by spray drying; heat treat the obtained powder in a mixed reducing atmosphere (a mixed atmosphere of hydrogen and argon), first calcine at 350°C for 8h and then heat to 800°C for 20h to obtain the lithium iron phosphate positive electrode material.

[0071] Example 4

[0072] The difference between this embodiment and embodiment 1 is that in this embodiment, the mass proportion of carbon quantum dots containing amino groups in the coating layer is 19.5%.

[0073] The rest of the preparation methods and parameters were the same as those in Example 1.

[0074] Example 5

[0075] The difference between this embodiment and embodiment 1 is that in this embodiment, the mass proportion of carbon quantum dots containing amino groups in the coating layer is 26.5%.

[0076] The rest of the preparation methods and parameters were the same as those in Example 1.

[0077] Example 6

[0078] The difference between this embodiment and embodiment 1 is that in step (2) of this embodiment, calcination is performed only once at a temperature of 700° C. for 6 hours.

[0079] The rest of the preparation methods and parameters were the same as those in Example 1.

[0080] Example 7

[0081] The difference between this embodiment and embodiment 1 is that in the preparation method of this embodiment, the ethylenediamine in step (1) is replaced by formamide (the number of amino groups is less than that in embodiment 1).

[0082] The rest of the preparation methods and parameters were consistent with those in the example.

[0083] Comparative Example 1

[0084] The difference between this comparative example and Example 1 is that the coating layer in this comparative example only has amorphous carbon and does not include carbon quantum dots containing amino groups.

[0085] In the preparation method, step (1) is not performed.

[0086] The rest of the preparation methods and parameters were the same as those in Example 1.

[0087] Comparative Example 2

[0088] The difference between this comparative example and Example 1 is that the coating layer in this comparative example does not contain amorphous carbon.

[0089] In step (2) of the preparation method, no sucrose carbon source is added.

[0090] The rest of the preparation methods and parameters were the same as those in Example 1.

[0091] Comparative Example 3

[0092] The difference between this comparative example and Example 1 is that the lithium iron phosphate positive electrode material provided in this comparative example does not contain a coating layer.

[0093] In the preparation method, step (1) is not performed and spray drying and coating are not performed.

[0094] The rest of the preparation methods and parameters were the same as those in Example 1.

[0095] Figure 1 A comparison of the cycle performance of the battery provided by Example 1 and Comparative Example 3 is shown. Figure 1 It can be seen that the lithium iron phosphate positive electrode material provided by the present invention can effectively enhance the material stability and improve the cycle performance through mixed coating of amorphous carbon and carbon quantum dots containing amino groups.

[0096] The lithium iron phosphate positive electrode material, Super P, and PVDF provided in Examples 1-7 and Comparative Examples 1-3 were mixed with an appropriate amount of NMP solvent in a mass ratio of 8:1:1 to prepare an electrode slurry, which was then evenly coated on an aluminum foil and then placed in a vacuum drying oven for drying. A slicer was used to prepare an electrode sheet with a diameter of 12 mm, and the lithium half-cell was assembled in a vacuum glove box filled with argon.

[0097] The batteries provided in Examples 1-7 and Comparative Examples 1-3 were subjected to electrochemical performance tests under the test conditions of 0.1C / 0.1C cycle test. The results are shown in Table 1.

[0098] Table 1

[0099]

[0100] From the data results of Example 1 and Examples 4 and 5, it can be seen that if there are too many carbon quantum dots containing amino groups in the coating layer, it is not conducive to the gram capacity, while if there are too few, the cycle performance will be affected.

[0101] It can be seen from the data results of Example 1 and Example 6 that the one-step heat treatment process is not conducive to the stability of the lithium iron phosphate material.

[0102] From the data results of Example 1 and Example 7, it can be seen that when different organic substances containing amino groups are selected, too few amino groups will affect the gram capacity and circulation of the material to a certain extent.

[0103] From the data results of Example 1 and Comparative Examples 1 and 2, it can be seen that amorphous carbon and carbon quantum dots containing amino groups are indispensable in the coating layer. Without carbon quantum dots, it is difficult to achieve long cycles, while only containing carbon quantum dots will lead to poor cycle performance.

[0104] It can be seen from the data results of Example 1 and Comparative Example 3 that if no coating is performed on the lithium iron phosphate matrix, the material stability will be seriously affected.

[0105] In summary, the lithium iron phosphate positive electrode material provided by the present invention includes carbon quantum dots containing amino groups and amorphous carbon in the coating layer, so that the coating is more uniform and the conductivity of lithium iron phosphate is improved. At the same time, the amino groups in the carbon quantum dots can stabilize the HF and water generated by the lithium ion battery during use, prevent HF and water from damaging the positive electrode material, extend the cycle life, and improve the structural stability, conductive agent and cycle stability of the lithium iron phosphate positive electrode material. The battery adopts the lithium iron phosphate material provided by the present invention, regulates the quality of the carbon quantum dots in the coating layer, and adopts a two-step heat treatment method. The initial specific capacity at 0.1C can reach more than 164.92mAh / g, and the capacity retention rate after 40 cycles can reach more than 83.5%.

[0106] The applicant declares that the above is only a specific implementation mode of the present invention, but the protection scope of the present invention is not limited thereto. Those skilled in the art should understand that any changes or substitutions that can be easily thought of by those skilled in the art within the technical scope disclosed by the present invention shall fall within the protection scope and disclosure scope of the present invention.

Claims

1. A lithium iron phosphate positive electrode material, characterized in that: The lithium iron phosphate positive electrode material comprises a lithium iron phosphate matrix and a coating layer coated on the surface of the lithium iron phosphate matrix; the coating layer comprises carbon quantum dots containing amino groups and amorphous carbon; The mass of the carbon quantum dots containing amino groups is 20-25% of the mass of the coating layer; The lithium iron phosphate positive electrode material is prepared by the following method, which comprises the following steps: The carbon quantum dots containing amino groups and the carbon source are coated on the surface of the lithium iron phosphate matrix by a spray drying method, and heat treated to obtain the lithium iron phosphate positive electrode material; The organic matter containing amino groups includes ethylenediamine and / or formamide; The heat treatment includes performing a primary heat treatment and a secondary heat treatment in sequence.

2. The lithium iron phosphate positive electrode material according to claim 1, characterized in that: The D50 of the carbon quantum dots containing amino groups is 2 to 5 nm.

3. The lithium iron phosphate positive electrode material according to claim 1, characterized in that: The D50 of the lithium iron phosphate is 600-700 nm.

4. The lithium iron phosphate positive electrode material according to claim 1, characterized in that: The mass of the coating layer is 0.1-0.2% of the mass of the lithium iron phosphate positive electrode material.

5. A method for preparing the lithium iron phosphate positive electrode material according to any one of claims 1 to 4, characterized in that: The preparation method comprises the following steps: The carbon quantum dots containing amino groups and the carbon source are coated on the surface of the lithium iron phosphate matrix by a spray drying method, and heat treated to obtain the lithium iron phosphate positive electrode material; The organic matter containing amino groups includes ethylenediamine and / or formamide; The heat treatment includes performing a primary heat treatment and a secondary heat treatment in sequence.

6. The method for preparing the lithium iron phosphate positive electrode material according to claim 5, characterized in that: The method for preparing the carbon quantum dots containing amino groups comprises: The organic matter containing amino groups is mixed with citric acid, subjected to hydrothermal reaction, and freeze-dried to obtain carbon quantum dots containing amino groups.

7. The preparation method according to claim 6, characterized in that: The temperature of the hydrothermal reaction is 100-220°C.

8. The preparation method according to claim 6, characterized in that: The hydrothermal reaction time is 12 to 24 hours.

9. The preparation method according to claim 6, characterized in that: The freeze-drying time is 24 to 48 hours.

10. The method for preparing a lithium iron phosphate positive electrode material according to claim 5, characterized in that: The coating method comprises: The iron source, phosphorus source and polyvinyl pyrrolidone are mixed, and the pH value is adjusted to obtain an iron phosphate solution. The iron phosphate solution, lithium source, carbon quantum dots containing amino groups and carbon source are mixed, and spray-dried for coating.

11. The method for preparing a lithium iron phosphate positive electrode material according to claim 10, characterized in that: The pH value is 3 to 3.

4.

12. The preparation method according to claim 10, characterized in that: The spray drying temperature is 170-180°C.

13. The method for preparing a lithium iron phosphate positive electrode material according to claim 5, characterized in that: The heat treatment is performed in a reducing atmosphere.

14. The preparation method according to claim 5, characterized in that: The temperature of the primary heat treatment is 300-350°C.

15. The preparation method according to claim 5, characterized in that: The time of the primary heat treatment is 5 to 8 hours.

16. The preparation method according to claim 5, characterized in that: The temperature of the secondary heat treatment is 600-800°C.

17. The preparation method according to claim 14, characterized in that: The time of the secondary heat treatment is 10 to 20 hours.

18. The method for preparing a lithium iron phosphate positive electrode material according to claim 5, characterized in that: The preparation method comprises the following steps: (1) mixing an organic substance containing an amino group with citric acid, hydrothermally reacting the mixture at 100 to 220° C. for 12 to 24 hours, and freeze-drying the mixture for 24 to 48 hours to obtain carbon quantum dots containing an amino group; (2) An iron source, a phosphorus source and polyvinyl pyrrolidone are mixed, and the pH value is adjusted to 3-3.4 to obtain an iron phosphate solution, and the iron phosphate solution, a lithium source, carbon quantum dots containing amino groups and a carbon source are mixed, spray-dried for coating, and then heat-treated at 300-350° C. for 5-8 h in a reducing atmosphere, and then heat-treated at 600-800° C. for 10-20 h to obtain the lithium iron phosphate positive electrode material.

19. A lithium ion battery, characterized in that: The lithium-ion battery comprises the lithium iron phosphate positive electrode material as claimed in any one of claims 1 to 4.

Citation Information

Patent Citations

  • Preparing method of lithium iron phosphate / carbon composite materials

    CN103384006A

  • Carbon-coated lithium iron phosphate and preparation method therefor, and lithium ion battery

    CN107240696A

  • Lithium ion battery phosphate-based composite cathode material and preparation method thereof

    CN105304881A

  • High-capacity core-shell amorphous carbon-based composite material, preparation method thereof and lithium ion battery containing high-capacity core-shell amorphous carbon-based composite material

    CN108448096A